Clinical study on the feasibility of new thrombus markers in predicting massive cerebral infarction - Zhao, Xiaoxia; Yang, Siyu; Lei, Ruining; Duan, Qiaoyan; Li, Jundong; Meng, Jiangtao; Sun, Lei (Frontiers in Neurology, 2023)
Objective This study investigated the diagnostic performance of thrombin-antiprothrombin complex (TAT), plasmin-α2 plasmin inhibitor complex (PIC), tissue plasminogen activator-plasminogen activator inhibitor complex (t-PAIC) and thrombomodulin (TM) in early identification of massive cerebral infarction. Method A total of 423 patients with cerebral infarction confirmed by imaging examination were divided into massive cerebral infarction group (MCI) and non-massive cerebral infarction group (NMCI). TAT, PIC, t-PAIC and TM were measured immediately after admission. The diagnostic performance was analyzed by receiver characteristic operating curve (ROC). Result The plasma concentrations of TAT, PIC, and t-PAIC in patients at early stage of MCI were higher than those in NMCI patients, and the difference was statistically significant (P < 0.001), and ROC curve analysis showed that PIC had the best performance in identifying MCI at early stage (area under the curve, AUC = 82.8%), with a sensitivity of 80.7% and a specificity of 76.2% when the PIC concentration was ≥0.8μg/mL; TAT had the highest specificity in identifying MCI, with a specificity of 80.6% when the TAT concentration was ≥3.97ng/mL. Conclusion The increased concentrations of TAT, PIC, and t-PAIC in patients at early stage of MCI have diagnostic value in identifying MCI patients and can be used as serum markers for early identification of macrovascular occlusion.